Characteristic of the indicators of the lower jaws in the brachycranial skull type. - Efimova, E. Yu.; Krayushkin, A. I.; Efimov, Yu. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The study of issues relating to the morphology and morphometry of dental arches, are relevant, defining the morphological and functional basis for the improvement and development of new diagnostic methods and interventions. Objective. The research is to study the characteristics of the parameters of the width of the mandibular dental arches with brachycranial skull type. Methods. The work was performed on 64 skull preparations of persons of mature age of both sexes with physiological occlusion of the teeth. According to the cranial index, all preparations belonged to brachycranial type skulls (cranial index from ≥ 80.0). The dental arch width was measured at the level of canines, premolars and molars at the established points of the vestibular and lingual contours. Results. The minimum and maximum variations and amplitudes of the dental arch width at various measurement levels are determined. Identified the identity of indicators of the dental arch width with the vestibular side of male and female at the level of the canines. The minimum and maximum dental arch from the vestibular side at the level of premolars and second molars, the dental arch width from the lingual side at the level of second premolars and both molars exceeded those of female. The dental arch width from the vestibular side at the level of the first molars, and the lingual side of male at the level of the canines were inferior to those of female. Conclusion. The study of the regularities of the parameters of the dental arches, taking into account the craniotype, is the basis for the correct understanding and interpretation of the studied quantities. As shown by our data, the average index of the mandibular dental arches width may prevail over the value of the minimum options, as well as be less than the value of the maximum options. This indicates the fact that the determination of more accurate boundaries of the physiological norm range of morphometric characteristics of dental arches may help reduce inaccuracies in the diagnosis and determine a treatment plan for various anomalies of the maxillofacial area.